2007
DOI: 10.2174/138161207782110462
|View full text |Cite
|
Sign up to set email alerts
|

The Development of New Concepts for Assessing Reproductive Toxicity Applicable to Large Scale Toxicological Programmes

Abstract: Large scale toxicological testing programmes which are currently ongoing such as the new European chemical legislation REACH require the development of new integrated testing strategies rather than applying traditional testing schemes to thousands of chemicals. The current practice of requiring in vivo testing for every possible adverse effect endanger the success of these programmes due (i) to limited testing facilities and sufficient capacity of scientific/technical knowledge for reproductive toxicity; (ii) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 48 publications
0
30
0
1
Order By: Relevance
“…two decades ago, luster et al (1992) investigated the relationship aspect cannot be satisfied without the use of additional animal groups savings in animals and costs will be minimal compared to the two-generation study. It has to be recalled that this represents one of the largest animal consuming tests and a key burden of the ReACH program Rovida and Hartung, 2009;Bremer et al, 2007;Rovida et al, 2011).…”
Section: Consideration 4: Is There Developmental Immunotoxicity?mentioning
confidence: 99%
“…two decades ago, luster et al (1992) investigated the relationship aspect cannot be satisfied without the use of additional animal groups savings in animals and costs will be minimal compared to the two-generation study. It has to be recalled that this represents one of the largest animal consuming tests and a key burden of the ReACH program Rovida and Hartung, 2009;Bremer et al, 2007;Rovida et al, 2011).…”
Section: Consideration 4: Is There Developmental Immunotoxicity?mentioning
confidence: 99%
“…In europe there is the Council of europe Convention etS 123 and european Community Directive 2010/63/eU, which will be enacted on January 1, 2013, and more internationally there are the Organization for economic Co-operation and Development (OeCD), (Bremer et al, 2007). this is already assessed in general toxicity repeat-dose studies and is easier to model in vitro than the whole reproductive cycle.…”
Section: Refinementmentioning
confidence: 99%
“…This is not what we see in the database of the US EPA for 2,000 HPV substances, where very little test information for reproductive toxicity is available (Bremer et al, 2007). Thus it appears that studies of lesser relevance have now been brought forward, but this cannot be confirmed at this stage.…”
Section: In Vitro Opportunitiesmentioning
confidence: 72%